2010
DOI: 10.1080/16843703.2010.11673226
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis and Robust Approach in Multidimensional Scaling: An Evaluation of Customer Satisfaction

Abstract: Multidimensional scaling (MDS) methods are devoted par excellence to representing a set of objects in a low-dimensional Euclidean space by preserving, as far as possible, the proximities between the objects themselves. Like other data analysis techniques, MDS methods treat a set of data as the entire population of interest. It is therefore important to determine the stability and robustness of the results against possible perturbations or errors present in the data. This issue is particularly important in cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…1, with the grouping of accessions was developed based on Gower's general similarity coefficient. This coefficient is suitable for the data with mixed of qualitative and quantitative attributes (Solaro, 2010). The dendrogram constructed using UPGMA method showed that two main clusters were formed.…”
Section: Resultsmentioning
confidence: 99%
“…1, with the grouping of accessions was developed based on Gower's general similarity coefficient. This coefficient is suitable for the data with mixed of qualitative and quantitative attributes (Solaro, 2010). The dendrogram constructed using UPGMA method showed that two main clusters were formed.…”
Section: Resultsmentioning
confidence: 99%
“…Weighting is used to handle the missing values, a weight w ijl = 0 when the observation between points i and j is not available. Finally, GCS give much weights to the qualitative variables, when the variables are heterogeneous, such as Gini's or Shannon's heterogeneity [Solaro 2010].…”
Section: Input Data For Mdsmentioning
confidence: 99%
“…DeLeeuw and Meulman (1986) have implemented a viable solution based on leave-one-out crossvalidation for tackling sensitivity issues in MDS as well as Linting et al (2007), and there is not much literature on this matter to date. Solaro (2010) presents an interesting application to customer satisfaction which is based on the latter approach for variables measured at different levels, for example, nominal, ordinal, or ratio scale. Despite a sensitivity study can also reveal possible influences of ''abnormal'' observations in a multivariate data analysis, there is a body of specific tools developed to search for multivariate outliers in data analysis.…”
Section: Are These Mds Configurations Stable and Robust?mentioning
confidence: 99%
“…However, when outliers come in batches the problem of masking may arise. In this sense, Solaro (2010) proposed to go deeper inside the structure of the data through the FS algorithm (Atkinson and Riani 2000;Riani et al 2009). As far as we know, there are still no contributions in literature which extend the applicability of FS to mixed-type data.…”
Section: Contaminating the Data Setmentioning
confidence: 99%
See 1 more Smart Citation